#FeesMustFall: An Internet-Age Student Movement in South Africa and the Case of the University of the Free State. (4th May 2017) - Luescher, Thierry; Loader, Lacea; Mugume, Taabo
ABSTRACT: How can we begin to make sense of the diversity of hashtag student movements that sprang up in South Africa in the course of 2015? In this paper we start by presenting key elements of Altbach's empirical theory of student movements and Castells' conceptualisation of internet-age networked movements to propose as conceptual point of departure the notion of 'internet-age student movement'. At the case of the campus-based #SteynMustFall and #UFSFeesMustFall student movement at the University of the Free State (UFS), we illustrate the richness of data available for empirical analysis and reflect on related methodological challenges when seeking to understand internet-age student movements and the dynamic relationship between the campus-based and the country-wide movement, the territorial space and the cyberspace. We conclude by reflecting on some elements of a possible research agenda for engaging with the 2015 South African hashtag student movements.